Bioassay-guided isolation of the antioxidant constituent from Kaempferia rotunda L. - DYAH ARYANTINI; PUJI ASTUTI; NUNUNG YUNIARTI; SUBAGUS WAHYUONO (Society for Indonesian Biodiversity, 2023)
Abstract. Aryantini D, Astuti P, Yuniarti N, Wahyuono S. 2023. Bioassay-guided isolation of the antioxidant constituent from Kaempferia rotunda L. Biodiversitas 24: 3641-3648. Kaempferia rotunda L. contains various phytochemical compounds with various biological activities and has been widely utilized in traditional medicine. This research focused on exploring bioactive compounds in the ethanol extract of Kaempferia rotunda using radical scavenging (1,1-Diphenyl-2-picrylhydrazyl) bioassay-guided isolation. Initially, the powdered material of K. rotunda was macerated with 70% ethanol and filtered, and the filtrate was evaporated in vacuo to make concentrated ethanol extract. The concentrated ethanol extract was then triturated gradually with increasing polarity of solvents (n-hexane, ethyl acetate, ethanol) to give n-hexane (HSF), ethyl acetate (EASF), ethanol (ESF), and residue (ISF) fractions. Each fraction was tested by DPPH bioassay with quercetin as the positive control to determine the active fraction. The active fraction (ESF) was further fractionated by Vacuum Liquid Chromatography (VLC) using a mobile gradient phase starting from ethyl acetate 100%, acetone 100%, and methanol 100% tomake3 sub-fractions (F1, F2, F3),respectively. The DPPH radical scavenging bioassay showed that F1 was the most active, containing bioactive compound detected by TLC visualized by DPPH. Based on spectroscopic and literature data comparison, this compound was isolated, purified, and identified ascrotepoxide. Crotepoxide displayed IC50of 38.91±0.59 (ABTS), 47.45±0.60 (DPPH),and 26.74±1.23 (FRAP) µg/mL.